Benefit of solid-liquid separation on volatile fatty acid production from grass clipping with ultrasound-calcium hydroxide pretreatment. (February 2019) - Wang, Siqi; Tao, Xue; Zhang, Guangming; Zhang, Panyue; Wang, Hongjie; Ye, Junpei; Li, Fan; Zhang, Qian; Nabi, Mohammad
Graphical abstract: Highlights: Solid-liquid separation fermentation effectively enhance VFA production. Total VFA yield and VS removal reached 515 mg/gTS and 59.7% from grass clipping. Modified Gompertz and first-order kinetic models fitted well with VFA production. Halocella and Ruminiclostridium play a key role for VFA production. Abstract: Ultrasound-calcium hydroxide (US-Ca(OH)2 ) pretreatment effectively enhanced volatile fatty acid (VFA) production from lignocellulosic biomass. In this paper, solid and liquid fraction of pretreated grass clipping was for the first time separately fermented in order to improve organic recovery from liquid fraction and reduce inhibition due to alkaline pretreatment. The total VFA yield and VS removal reached 515 mg/g TS and 59.7% after solid-liquid separation, exhibiting an increase of 116.7% and 91.9% comparing to that of mixture sample. The dominate components of VFAs are acetic and propionate acid, accounting for 80–90% of total VFAs. Kinetic analysis showed that the highest maximum VFA production rate of 690 mg/L·d and the highest cumulative VFA production potential of 3299 mg/L were achieved in the fermentation of solid fraction. Microbial analysis showed that the dominate genera for VFA production were Halocella and Ruminiclostridium, both with a relative abundance of 20.1% in fermentation of solid fraction.